A high-performance anode for lithium ion batteries: Fe3O4 microspheres encapsulated in hollow graphene shells1. Issue 22 (14th June 2015) - Jiang, Yu; Jiang, Zhong-Jie; Yang, Lufeng; Cheng, Shuang; Liu, Meilin
<x xml:space="preserve">Abstract</x> A composite electrode composed of Fe3O4 microspheres encapsulated in hollow graphene shells exhibits high electrochemical performance when used as an anode in a lithium ion battery.